g-C3N4 quantum dots decorated spherical Bi2WO6 photocatalyst and its enhanced photocatalytic activities mechanism - GUO Li; ZHANG Kai-lai; ZHANG Xin; ZHAO Fang-li; ZHAO Qiang; YANG Xiao; WANG Dan-jun; FU Feng (Cailiao gongcheng, 2019)
Three-dimensional(3D) Bi2WO6 architecture was successfully synthesized via a hydr-othermal process. The g-C3N4 quantum dots(QDs) were deposited on the surface of as-synthesized 3D Bi2WO6 hierarchical structure to construct the novel Z-scheme g-C3N4/Bi2WO6 heterojunctions via a simple impregnation-calcination method. The morphology, composition and visible-absorptive properties of as-synthesized samples were characterized by XRD, FE-SEM, TEM, UV-Vis-DRS techniques. Methylene blue(MB) and p-nitrophenol(p-NPh) were selected as model pollutant to investigate the effect of g-C3N4 QDs on the photocataytic activity of Bi2WO6 nanoarchitecture. The results reveal that as-prepared Bi2WO6 exhibits the 3D architecture with the pore size of about 10nm via a simple impregnation-calcination method. g-C3N4 QDs with the size of about 5nm can be deposited on the surface of secondary nanoplate of Bi2WO6. The photocatalytic activity of Z-scheme g-C3N4/Bi2WO6 is superior to the pure g-C3N4 and Bi2WO6, and 10%g-C3N4/Bi2WO6 exhibits the best photocatalytic activity for MB and p-NPh. The apparent rate constant (kapp) for the degradation of MB is as high as 4.5 and 5.8 times, 2.6 and 1.6 times for p-NPh compared to that of pure g-C3N4 and Bi2WO6, respectively. The O2·- is the main reactive species during the photocatalytic process. The catalytic efficiency enhancement of g-C3N4/Bi2WO6 relative to Bi2WO6 or g-C3N4 can be attributed to the formation of heterojunction between g-C3N4 QDs and Bi2WO6, which suppresses the recombination of photogenerated electron/hole pairs as well as broaden the light absorption.